2014
DOI: 10.1007/s10584-014-1294-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate uncertainty and economic development: evaluating the case of Mozambique to 2050

Abstract: We apply a probabilistic approach to the evaluation of climate change impacts in Mozambique. We pass a distribution of climate shocks through a series of structural biophysical models. The resulting joint distributions of biophysical outcomes are then imposed on a dynamic economywide model. This framework produces distributions of economic impacts of climate change thus identifying an explicit range of potential economic outcomes and associating probability levels with given sets of outcomes. For example, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
(11 reference statements)
2
18
0
Order By: Relevance
“…Finally, the model contains a detailed sector breakdown and provides a "simulation laboratory" for quantitatively examining how the individual impact channels of climate change influence the performance and structure of the whole economy. For these reasons, economy-wide assessments, already a main workhorse for mitigation policies, are increasingly used to consider climate change impacts and adaptations (e.g., [15][16][17][18]). …”
Section: Economy-wide Modeling Frameworkmentioning
confidence: 99%
“…Finally, the model contains a detailed sector breakdown and provides a "simulation laboratory" for quantitatively examining how the individual impact channels of climate change influence the performance and structure of the whole economy. For these reasons, economy-wide assessments, already a main workhorse for mitigation policies, are increasingly used to consider climate change impacts and adaptations (e.g., [15][16][17][18]). …”
Section: Economy-wide Modeling Frameworkmentioning
confidence: 99%
“…For Southern Africa, the median decline was estimated to be -11% with the most significant decline occurring for maize crops. Using an integrated modelling framework, research by UNU-WIDER has assessed the impacts of climate change on a number of sub-Saharan African countries including Malawi, Mozambique, Tanzania, and Zambia (see, for example, and Arndt and Thurlow 2013). The findings from these studies have shown that climate change impacts on economic growth and development are expected to be negative, especially if global mitigation fails to emerge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This formal treatment of uncertainty is very valuable in the context of impact analysis in that, with the further modelling efforts described in Figure 1, it permits one to develop ranges of biophysical and economic outcomes. As noted by Arndt and Thurlow (2013), this represents a substantial step forward from a policy analysis perspective. Analyses to date have normally provided a limited number of impact scenarios with no measure of likelihood associated with each scenario.…”
Section: Global Changementioning
confidence: 92%